The European General Data Protection Regulation: challenges and considerations for iPSC researchers and biobanks. (September 2017) - Morrison, Michael; Bell, Jessica; George, Carol; Harmon, Shawn; Munsie, Megan; Kaye, Jane
Increasingly, human induced pluripotent stem cells (iPSC) and their associated genetic and clinical information are being used in a wide range of applications, with large biobanks being established to support and increase their scientific use. The new European General Data Protection Regulations, which comes into effect in 2018, will have implications for biobanks that generate, store and allow research access to iPSC. This paper describes some of the challenges that iPSC biobanks face and suggests some points for the development of appropriate governance structures to address these new requirements. These suggestions also have implications for iPSC research in general.